Assessing the effectiveness of the methods adopted by faith based organisations in reducing poverty in Zimbabwe: case study of the diocese of Mutare Community Care Programme (DOMCCP) in Nyanga, Nyakomba from 2007-2016. - Nyagomo, Kelvin (Midlands State University, 2018)
The study is an assessment of the methods adopted by Faith Based Organisations (FBOs) in reducing poverty in Zimbabwe using Diocese of Mutare Community Care Programme (DOMCCP) as a case study in Nyanga, Nyakomba ward 11. The research findings show that DOMCCP’s interventions as a Faith Based Organisation impacted positively on the rural livelihood of the people who live in Nyakomba ward 11. DOMCCP addressed poverty through livelihood projects, capacity building and community health, gender mainstreaming and human rights. DOMCCP intervention reduces poverty in Nyakomba by assisting people living with HIV/AIDS to access home based care, to have nutritional food to enhance their quality of life at the same time eradicating poverty. The study however finds that DOMCCP as a Faith Based Organisation have a number of challenges in trying to implement their projects of eradicating poverty in Nyakomba. Sustainable Rural Livelihood approach was used as a theory to analyze the livelihoods of people and see how best these can be changed. The research finally recommends DOMCCP and other Faith Based Organisation to provide more supportive projects targeting OVCs and PLWH since they are the most vulnerable groups in the community.